Expression of proton‐coupled oligopeptide transporter (POTs) in prostate of mice and patients with benign prostatic hyperplasia (BPH) and prostate cancer (PCa). Issue 3 (9th August 2012) - Sun, Dongli; Tan, Fuqing; Fang, Danbo; Wang, Yuqing; Zeng, Su; Jiang, Huidi
Abstract BACKGROUND Proton‐coupled oligopeptide transporters (POTs) serve as integral membrane protein for the cellular uptake of di/tripeptide. Prostate has a large requirement of nutriment for its function to produce and secrete prostatic fluid. Besides, prostate suffered from limited therapy effect of drug treatment. Thus present study was performed to evaluate the expression of POTs in prostate of mice and human with the aim to provide information for potential role of POTs in absorption of nutriment and peptidomimetic drugs in prostate. METHODS Quantitative real‐time polymerase chain reaction (qRT‐PCR) and Western blot methods were applied to study the mRNA, protein expression of POTs in prostate, human prostate cancer cells (PC‐3), and human prostate epithelial cells (RWPE‐1). RESULTS qRT‐PCR study showed different characteristic of POTs mRNA expression in mouse prostate. Among these transporters, protein expression of PepT2 was detected and increasing during the development of mouse prostate, while PepT1, PHT1, and PHT2 protein was not detected. Furthermore, different characteristic of regulation by inflammation on POTs mRNA expression was found in RWPE‐1 and PC‐3. In addition, mRNA expression of PepT2 and PHT1 in prostate of patients with PCa was demonstrated be lower compared with BPH. CONCLUSIONS These findings provide the first evidence for the expression of POTs in prostate of mice and patients with BPH or PCa and suggest that POTs are likely to play a role in the transport of di/tripeptides and peptidomimetics in prostate. Prostate 73: 287–295, 2013. © 2012 Wiley Periodicals, Inc.